Lipoteichoic acid challenge induces higher inflammatory responses than lipopolysaccharide in UV irradiated keratinocytes - Cela, Eliana Maiten (2015)
In the present work, we aimed to evaluate how UVR exposure could affect keratinocytes antimicrobial inflammatory response to gram-positive and gramnegative bacteria components, such as LTA and LPS. We observed that UVR increased keratinocytes responsiveness to microbial external components. Interestingly, this response was more intense to LTA than to LPS, in contrast to the response commonly observed in other cell types like macrophages, where the immune response is bias towards gram-negative bacteria. This increase in the response to microbial components, especially to LTA, was only partially observed in VitD3- treated cells showing that other molecules might also be involved in this response. The preferential recognition of gram-positive bacteria can be considered as a specialization of the epithelium to its microflora. If this epithelium suffers an injury (like exposure to harmful radiation), it has to modify its response to microorganisms in order to avoid their entry into sites where they might produce infections. In this context, the increment in the inflammatory response observed in UVR-irradiated LTA challenged keratinocytes is a novel evidence to understand the complex balance between the skin, its microflora and the environment.